2013
DOI: 10.1073/pnas.1307301110
|View full text |Cite
|
Sign up to set email alerts
|

Cranial irradiation compromises neuronal architecture in the hippocampus

Abstract: Cranial irradiation is used routinely for the treatment of nearly all brain tumors, but may lead to progressive and debilitating impairments of cognitive function. Changes in synaptic plasticity underlie many neurodegenerative conditions that correlate to specific structural alterations in neurons that are believed to be morphologic determinants of learning and memory. To determine whether changes in dendritic architecture might underlie the neurocognitive sequelae found after irradiation, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
199
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 190 publications
(230 citation statements)
references
References 44 publications
24
199
0
Order By: Relevance
“…Radiation is well known for its neurotoxic effects, including alteration of neural progenitor cell function, increased apoptotic cell death throughout the brain (including white matter), and impaired hippocampal function (10,12,40,41), a brain area critically relevant for maintenance of learning and memory and regulation of mood and anxiety (42-49). jci.org Volume 128 Number 1 January 2018…”
Section: Discussionmentioning
confidence: 99%
“…Radiation is well known for its neurotoxic effects, including alteration of neural progenitor cell function, increased apoptotic cell death throughout the brain (including white matter), and impaired hippocampal function (10,12,40,41), a brain area critically relevant for maintenance of learning and memory and regulation of mood and anxiety (42-49). jci.org Volume 128 Number 1 January 2018…”
Section: Discussionmentioning
confidence: 99%
“…Our past studies have shown that cranial irradiation could significantly disrupt components of neuronal architecture including dendritic length, volume, and complexity (13,14). To determine the potential impact of MV grafting on neuronal structure, Golgi-Cox-impregnated sections were used in detailed morphometric analyses of GCL neurons in the DG.…”
Section: Object In Placementioning
confidence: 99%
“…55 The increased expression of the postsynaptic protein PSD-95 found in this study is in agreement with the results observed by Parihar and Limoli after cranial irradiation with doses of 1 Gy and 10 Gy. 56 PSD-95 is involved in the development, outgrowth, branching and maturation of dendritic spines and modulation of synaptic signals. 57,58 Elevated PSD-95 levels alter the ratio of excitatory to inhibitory synaptic contacts and thus neuronal excitability, a typical event in the pathobiology of several neurodegenerative diseases.…”
Section: Irradiation Affects Synapse Morphology By Targeting the Rac1mentioning
confidence: 99%